1-Nitropyrene disrupts testosterone biogenesis via AKAP1 degradation promoted mitochondrial fission in mouse Leydig cell. (15th August 2022) - Zhang, Wei-wei; Li, Xiu-liang; Liu, Yu-lin; Liu, Jia-yu; Zhu, Xin-xin; Li, Jian; Zhao, Ling-li; Zhang, Cheng; Wang, Hua; Xu, De-xiang; Gao, Lan
Abstract: Previous study found 1-NP disrupted steroidogenesis in mouse testis, but the underlying mechanism remained elusive. The current work aims to explore the roles of ROS-promoted AKAP1 degradation and excessive mitochondrial fission in 1-NP-induced steroidogenesis disruption in MLTC-1 cells. Transmission electron microscope analysis found 1-NP promoted excessive mitochondrial fission. Further data showed 1-NP disrupted mitochondrial function. pDRP1 (Ser637), a negative regulator of mitochondrial fission, was reduced in 1-NP-treated MLTC-1 cells. Mechanistically, 1-NP caused degradation of AKAP1, an upstream regulator of pDRP1 (Ser637). MG132, a proteasome inhibitor, attenuated 1-NP-induced AKAP1 degradation and downstream pDRP1 (Ser637) reduction, thereby ameliorating 1-NP-downregulated steroidogenesis. Further analysis found that cellular ROS was elevated and NOX4, HO-1 and SOD2 were upregulated in 1-NP-exposed MLTC-1 cells. NAC, a well-known commercial antioxidant, alleviated 1-NP-induced excessive ROS and oxidative stress. 1-NP-induced AKAP1 degradation and subsequent downregulation of pDRP1 (Ser637) were prevented by NAC pretreatment. Moreover, NAC attenuated 1-NP-resulted T synthesis disturbance in MLTC-1 cells. The present study indicates that ROS mediated AKAP1 degradation and subsequent pDRP1 (Ser637) dependent mitochondrial fission is indispensable in 1-NP caused T synthesis disruption. This study provides a new insight into 1-NP-induced endocrine disruption, and offers theoretical basis in public health prevention. Graphical abstract: Image 1 Highlights: 1-NP reduces pDRP1 (Ser637) and exacerbates mitochondrial fission in MLTC-1 cells. 1-NP induces AKAP1 ubiquitin degradation in MLTC-1 cells. Proteasome inhibitor alleviates 1-NP-induced steroidogenesis disruption in MLTC-1 cells. NAC pretreatment attenuates 1-NP-induced AKAP1 degradation and steroidogensis disruption.